KETERAMPILAN GURU DALAM PENGELOLAAN KELAS - Nova Yanti (STAI Hubbulwathan Duri, 2015)
Teacher in the classroom activities include two main things, namely teaching and managing classes. Teaching activities directly intended to intensify students achieve goals such as studying the needs of students, preparing lesson plans, presenting teaching materials to students, asking questions to the students, assessing student progress are examples of teaching activities. Manage classroom activities intended to create and sustain an atmosphere (condition) that the class teaching activities that can take place effectively and efficiently. Rewarded with immediate effect, develop a good relationship between teachers and students, develop rules of the game in the group's activities are examples of activities to manage the class. Failure of a person achieve the learning objectives of teachers is directly proportional to the inability of teachers to manage classes. An indicator of the failure of such a low student learning achievement, not in accordance with the standards or the size limit specified. Therefore, classroom management is a very important teacher competence